Imagery types of athletes in different sports - Kizildag, E.; Tiryaki, M. S. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The main purpose of this study was to compare the imagery use of elite male and female athletes in different sport types. Imagery has been defined as; "creation or re- creation of an experience generated from memorial information, involving quasi-sensorial, quasi-perceptual and quasi-affective characteristics, which is under the volitional control of imager, and it may occur in the absence of the real stimulus antecedents normally associated with the actual experience" (Morris etc. 2005). Hall etc. (1998) developed the Sport Imagery Questionnaire (SIQ) to assess the frequency with which athletes use these imagery functions. These functions are: cognitive specific-CS, cognitive general-CG, motivational specific-MS, motivational general-arousal-MG-A, motivational general-mastery-MG-M. Methods:186 athletes (122male and 64 female) from 6 various sports (volleyball, basketball, soccer, track and field, tennis, swimming), aged between 15 to 33 years (Mage= 21. 25± 3. 42) participated in the study. We used SIQ (Hall, etc., 1998). SIQ consists of 5 subscales (CS, CG, MS, MG-A, MG-M) and 30 items. In Turkish version of SIQ has supported the Questionnaire`s 4 factor structure and 21 items. To determine if there was a difference between male and female athletes we used to data Kruskall Wallis. Results: Results of this study there was a significant difference in MS subscale (p< .05). To determine the source of the difference we used Mann- Whitney U test. In this test result female volleyball and female basketball players had significantly higher score than tennis players in MS (Uvolleyball-tennis= 34.5, p< .05; U basketball-tennis= 19.0, p< .05). It was also found that male volleyball players had higher scores than soccer players in CI (Uvoleyball-soccer= 188.0, p< .01),male swimmers had significantly scores than male basketball players in MG-A (Uswimmingbasketball= 59.5, p< .05). Discussion: In literature review we were not run across imagery studies that compare gender. Generally in compare sport types male- female distinction didn`t find. Male volleyball players had higher scores than soccer players in CI. The reason of this difference the soccer player more amateur group than volleyball players in our study. Salmon etc. (1994) found elite soccer players used imagery more than novice and found they used motivational dimension more than cognitive. Isaac, Marks (1994) and Gammage etc. (2000) studies showed there were imagery differences existed based on gender and type of activity.